1998
DOI: 10.1557/jmr.1998.0027
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric properties of dielectrophoretically assembled particulate-polymer composites

Abstract: The dielectrophoretic effect is a phenomenon in which dipole-dipole interactions are induced between particles in a suspension by an electric field.1−5 This dipole interaction leads to the formation of chains or fibrils parallel to the applied electric field. Recently, the dielectrophoretic effect has been shown to be a possible composite assembly technique permitting property changes to be induced with the appropriate electric fields.6,7 The results presented in this paper show that the dielectrophoretic asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
109
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 88 publications
(113 citation statements)
references
References 11 publications
3
109
0
1
Order By: Relevance
“…28,[31][32][33] It has also been demonstrated that alignment of high aspect ratio particles increases the permittivity of the composite. 8,34,35 The calculated values correspond well with the experimental values of composites with low aspect ratios but tend to fall short for composites with higher aspect ratios. This is possibly due to the contribution of the large aspect ratio fibers.…”
Section: Permittivity and Piezoelectric Properties Of The Compositessupporting
confidence: 67%
See 4 more Smart Citations
“…28,[31][32][33] It has also been demonstrated that alignment of high aspect ratio particles increases the permittivity of the composite. 8,34,35 The calculated values correspond well with the experimental values of composites with low aspect ratios but tend to fall short for composites with higher aspect ratios. This is possibly due to the contribution of the large aspect ratio fibers.…”
Section: Permittivity and Piezoelectric Properties Of The Compositessupporting
confidence: 67%
“…The series-parallel model for dielectric properties of structured piezoelectric composites, introduced by Bowen et al, 8 assumes perfectly intact chains of particles with equidistant spacing. This modification of the well known mixing rule for 1-3 composites includes a specific particle spacing parameter and has been adapted for piezoelectric properties of these materials.…”
Section: Aligned Ellipsoidal Particles In Compositesmentioning
confidence: 99%
See 3 more Smart Citations